Pelatihan Pemanfaatan Microsoft Power Point sebagai Video Pembelajaran Matematika untuk Membantu Pembelajaran secara Daring bagi Guru-Guru MGMP Matematika SMP/MTs Kota Pekanbaru - Sagita Charolina Sihombing; Alyauma Hajjah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2022)
This community service was carried out at SMP Negeri 42 Pekanbaru City with the participants of the activity is MGMP Mathematics teachers for SMP/MTS Pekanbaru City. This activity is motivated by the fact that there has never been any socialization or training on the use of Microsoft Power Point to help online learning for Mathematics MGMP teachers. Microsoft power point is only used for presentations at seminars or delivering material face-to-face in front of the class. Therefore, it is necessary to hold a training activity on the use of Microsoft power point to help online learning for MGMP Mathematics teachers at SMP/MTs Pekanbaru City. This activity aims to provide material about the ideal slide size for online delivery, criteria for teaching material slides, and video making guidelines using Microsoft power point. The results of community service show that most of the training participants can receive the training materials well and can use Microsoft power point to make online learning videos.